1987
DOI: 10.1037/0735-7044.101.2.272
|View full text |Cite
|
Sign up to set email alerts
|

The central representation of an aversive event maintains the opioid and nonopioid forms of analgesia.

Abstract: Exposure to an aversive event, such as shock, can elicit either an opioid or nonopioid analgesia in rats. We suggest that the central representation of an aversive event in working memory activates both forms of analgesia. We formalize this basic hypothesis by coupling it with a current model of animal learning and memory, SOP (Wagner, 1981). SOP is designed to capture the standard operating procedures that govern memory systems. Our application of SOP suggests that manipulations which disrupt the maintenance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
193
4

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(212 citation statements)
references
References 81 publications
15
193
4
Order By: Relevance
“…As Millan (2002) points out in his extensive review of the descending control of pain, the difference in the mechanisms of facilitation and inhibition of nociception are primarily in receptor subtypes coupled to differing intracellular mechanisms. Spinal pathways, through mechanisms elaborated from the gate-control theory, and supraspinal descending inhibitory pain pathways, both play a role in mediating SIA (Grau, 1987;Grau et al, 1990;Madden et al, 1977;Meagher et al, 1993;Meagher et al, 1990;Rhudy et al, 2004;. Nociceptive information is then relayed either directly to the cortex or indirectly to the cortex through the brainstem, midbrain, and thalamus via the ascending pain pathways (for review see Millan, 1999).…”
Section: Neural Substrates Involved In Siamentioning
confidence: 99%
“…As Millan (2002) points out in his extensive review of the descending control of pain, the difference in the mechanisms of facilitation and inhibition of nociception are primarily in receptor subtypes coupled to differing intracellular mechanisms. Spinal pathways, through mechanisms elaborated from the gate-control theory, and supraspinal descending inhibitory pain pathways, both play a role in mediating SIA (Grau, 1987;Grau et al, 1990;Madden et al, 1977;Meagher et al, 1993;Meagher et al, 1990;Rhudy et al, 2004;. Nociceptive information is then relayed either directly to the cortex or indirectly to the cortex through the brainstem, midbrain, and thalamus via the ascending pain pathways (for review see Millan, 1999).…”
Section: Neural Substrates Involved In Siamentioning
confidence: 99%
“…They, and others, have reported that descending inhibitory systems are suppressed by barbiturates (Frank and Ohta 1971;Collins et al 1990). Since these reports, others showed that pentobarbital blocks shock-induced analgesia (Terman et al 1984;Grau 1987) and other forms of anesthesia were shown to diminish the inhibition of dorsal horn neuron firing seen after noxious stimulation (Tomlinson et al 1983). The exact mechanism through which this occurs remains unknown, although the inhibitory neurotransmitter GABA appears to play a major role (Asana and Ogasawara 1981;Olsen and Snowman 1982;Sivam et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible that the analgesia at these time points is a nonassociatively derived reaction that is induced by the initial analgesic reaction as a consequence of that reaction. Alternatively, the shock itself may produce a biphasic reaction with one type followed by the other type (Grau, 1987b). Perhaps removing the subjects from the shock environment and placing them in a new environment led to the appearance of only the first analgesia not because the second reaction required shock cues, but because the removal and placement in the new environment disrupted the sequential processes.…”
Section: Resultsmentioning
confidence: 99%
“…Fanselow is explicit that his position is restricted to the outcome of procedures using small numbers of shocks (Fanselow, 1986). Grau (1987aGrau ( , 1987b has also emphasized the role of associative processes. Here, analgesia is placed within the context of Wagner's SOP model of associative processes (Wagner, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation